2020
DOI: 10.1186/s12916-019-1483-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients with positive malaria tests not given artemisinin-based combination therapies: a research synthesis describing under-prescription of antimalarial medicines in Africa

Abstract: Background: There has been a successful push towards parasitological diagnosis of malaria in Africa, mainly with rapid diagnostic tests (mRDTs), which has reduced over-prescribing of artemisinin-based combination therapies (ACT) to malaria test-negative patients. The effect on prescribing for test-positive patients has received much less attention. Malaria infection in endemic Africa is often most dangerous for young children and those in low-transmission settings. This study examined non-prescription of antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Since 2010, despite the increased availability of parasitological diagnostics and ACT, studies among outpatients have reported sub-optimal health workers' compliance with 'test and treat' malaria guidelines [9][10][11][12][13][14][15][16][17][18][19][20][21][22], including poor ACT dosing, dispensing and counselling practices [10,17,[22][23][24]. These studies have been undertaken on a small, often single facility sample [16,19,21,23,[25][26][27]; at a single point of time [9, 10, 13, 15-17, 22, 23, 28]; have measured only a few indicators (e.g., treatment practices only) [14,20,25,29,30], or were limited to specific outpatient groups (e.g., children only) [12,13,19,26,28,29,31]. Several larger outpatient studies have suggested improvements in specific compliance indicators, such as testing of febrile patients or compliance with test-negative results [17,22,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, despite the increased availability of parasitological diagnostics and ACT, studies among outpatients have reported sub-optimal health workers' compliance with 'test and treat' malaria guidelines [9][10][11][12][13][14][15][16][17][18][19][20][21][22], including poor ACT dosing, dispensing and counselling practices [10,17,[22][23][24]. These studies have been undertaken on a small, often single facility sample [16,19,21,23,[25][26][27]; at a single point of time [9, 10, 13, 15-17, 22, 23, 28]; have measured only a few indicators (e.g., treatment practices only) [14,20,25,29,30], or were limited to specific outpatient groups (e.g., children only) [12,13,19,26,28,29,31]. Several larger outpatient studies have suggested improvements in specific compliance indicators, such as testing of febrile patients or compliance with test-negative results [17,22,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Mbonye et al in their research among private clinics and drug shops found that children with normal respiratory rates received unnecessary antibiotics for pneumonia [44], while Kjaergaad et al found inappropriate prescription rate of antibiotics for viral upper respiratory tract infections of 23-68% in Uganda and other countries across the globe [45]. Other studies carried out in private and public health facilities in Uganda and other African countries found that 7-24% children testing positive for malaria never received the correct malaria medicine [46,47]. In a study from Nigeria, over 85% of children with watery diarrhea were given unnecessary antibiotics, while in a study from Ethiopia, the assessment, as well as treatment of children for cough, fever, and diarrhea in clinics was of poor quality [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The use of injectable antimalarials in the current study is in contrast to findings from other settings. ACT Consortium studies across five countries found a substantial proportion of patients with confirmed uncomplicated malaria receiving drugs other than ACTs; but most commonly amodiaquine, chloroquine or SP rather than injectable antimalarials [ 19 ]. Two studies in Sudan identified relatively high proportions of children with uncomplicated malaria receiving injectable quinine [ 36 ], but with receipt of injectables more frequent in those over five than under 5 years [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations in case management identified by previous studies included failure to perform diagnostic testing on all suspected malaria cases [13][14][15], prescription of antimalarial drugs for test negative patients [14,16,17], or ACT not being prescribed to patients with confirmed malaria [18,19]. Additional shortcomings in other settings include 'poly-pharmacy' whereby multiple antimalarials are given at once, incorrect dose prescription [13,20], and lack of referral/admission or pre-referral treatment for severe malaria [21].…”
Section: Introductionmentioning
confidence: 99%